Ideal esthetic and functional full-thickness lower eyelid "like with like" reconstruction using a combined Hughes flap and swing skin flap technique. Issue 11 (November 2021) - Yano, Tomoyuki; Karakawa, Ryo; Shibata, Tomoyoshi; Fuse, Yuma; Suzuki, Akiyo; Kuramoto, Yukiko; Suesada, Nobuko; Miyashita, Hiroki; Yoshimatsu, Hidehiko
Summary: Background: A goal in ideal lower eyelid reconstruction is to achieve not only an esthetic recovery of the shape of the eyelid but also to obtain satisfactory eyelid function without damage to the corneal surface. In this report, we introduce our "Like with Like" reconstruction technique using a combined Hughes flap and swing skin flap. The Hughes flap is a tarsoconjunctival pedicled flap from the upper eyelid, and the swing skin flap is a kind of transposition flap based on the orbicularis muscle pedicle. Patients and methods: Eight patients who had more than 25% of the lower eyelid affected by a full-thickness defect were included. There were five men and three women, and the average age was 68.4years old. All patients had undergone wide tumor excision of the lower eyelid due to a malignant tumor and had also had primary two-stage eyelid reconstruction with a combined Hughes flap and swing skin flap. Results: The average reconstructive time was 1:20, and no postoperative severe complications such as flap necrosis or wound dehiscence were observed. The follow-up period was an average of one year, and there were no functional problems such as ectropion, lower eyelid retraction, lid margin hypertrophy, lacrimation disorder, or corneal problems observed in any cases. Esthetically, no reconstructed eyelid bulging or asymmetry in the lid margin was observed in any of the cases. Conclusions: Combining the Hughes flap and skin swing flap technique might be the best choice for a full-thickness lower eyelid defect with regard to the esthetic and functional results.